2021
DOI: 10.1007/s00423-021-02325-3
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of stress ulcer prophylaxis in a surgical patient cohort in a German university hospital

Abstract: Introduction Stress ulcer prophylaxis (SUP) has been a widespread practice both in intensive care units (ICU) and internal wards at the beginning of the twenty-first century. Clinical data suggests an important overuse of acid suppressive therapy (AST) for this indication. Data on current clinical practice of SUP in surgical patients in a non-ICU setting are spares. In the light of a growing number of reports on serious side effects of AST, this study evaluates the use of AST for SUP in a normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…This finding indicates the presence of significant uncertainty surrounding the correct indication for SUP. Moreover, in our survey, the risk for stress ulcer-related bleeding was massively overestimated, confirming previous findings indicating that although the relative risk of developing stress ulcer-related bleeding can be correctly assessed by the treating physician, the absolute risk is generally overestimated [25]. Compared with previous surveys, which showed a critical overestimation of the incidence of stress ulcer-induced bleeding in less than 50% of participants, the current investigation revealed a far more pronounced overestimation rate of 64.9%.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding indicates the presence of significant uncertainty surrounding the correct indication for SUP. Moreover, in our survey, the risk for stress ulcer-related bleeding was massively overestimated, confirming previous findings indicating that although the relative risk of developing stress ulcer-related bleeding can be correctly assessed by the treating physician, the absolute risk is generally overestimated [25]. Compared with previous surveys, which showed a critical overestimation of the incidence of stress ulcer-induced bleeding in less than 50% of participants, the current investigation revealed a far more pronounced overestimation rate of 64.9%.…”
Section: Discussionsupporting
confidence: 90%
“…In a mixed medical-surgical patient population, Parente et al reported the start of ASM in 37% of patients upon admission to the hospital [11]. Our research group recently assessed the ASM prescription routine for SUP on non-ICU surgical wards in a German university hospital: SUP was initiated in 40.3% of patients admitted to the normal surgical ward, and for 85.7-99.6% of those patients, no adequate indication for SUP could be identified retrospectively [25]. Thus, although the first report on the non-indicated over-prescription of ASM for SUP was published more than 20 years ago [1], and although a plethora of literature documents this phenomenon in medical and intensive care patients, current surgical perioperative practice seems as yet unaffected by this scientific evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations